Effect of N‐acetylcysteine on liver recovery after resection: A randomized clinical trial. Issue 4 (15th June 2016) - Grendar, Jan; Ouellet, Jean F.; McKay, Andrew; Sutherland, Francis R.; Bathe, Oliver F.; Ball, Chad G.; Dixon, Elijah
Abstract : Background and Objectives: Liver failure following hepatic resection is a multifactorial complication. In experimental studies, infusion of N‐acetylcysteine (NAC) can minimize hepatic parenchymal injury. Methods: Patients undergoing liver resection were randomized to postoperative care with or without NAC. No blinding was performed. Overall complication rate was the primary outcome; liver failure, length of stay, and mortality were secondary outcomes. Due to safety concerns, a premature multivariate analysis was performed and included within the model randomization to NAC, preoperative ASA, extent of resection, and intraoperative vascular occlusion as factors. Results: Two hundred and six patients were randomized (110 to conventional therapy; 96 to NAC). No significant differences were noted in overall complications (32.7% and 45.7%, P = 0.06) or hepatic failure (3.6% and 5.4%, P = 0.537) between treatment groups. There was significantly more delirium within the NAC group (2.7% and 9.8%, P < 0.05) that caused early trial termination. In multivariate analysis, only randomization to NAC (OR = 2.21, 95%CI = 1.16–4.19) and extensive resections (OR = 2.28, 95%CI = 1.22–4.29) were predictive of postoperative complications. Conclusions: Patients randomized to postoperative NAC received no benefit. There was a trend toward a higher rate of overall complications and a significantly higher rate of delirium in the NAC group. J. Surg. Oncol. 2016;114:446–450 . © 2016 Wiley Periodicals, Inc.